An Evaluation of the Interfacial Bond Strength of Kenaf Fibrous Concrete and Plain Concrete Composite - Ogunbode Ezekiel Babatunde (International Journal of Built Environment and Sustainability, 2019)
The deterioration of concrete structures is a matter of critical concern as it threatens the durability and strength of concrete structures. Kenaf fibrous concrete composite (KFCC) can be used with advantage in new structures such as precast elements, as well as the strengthening, repair and rehabilitation of old structures to improve their durability properties. These structures are composite components, with parts as Plain concrete (PC) and others as KFCC. This study, therefore, investigated the interfacial bonding behaviour between KFCC and PC. Shear, tensile and compressive tests were carried out to measure the bond strength in shear, direct tension and compression respectively for PC to PC, PC to KFCC and KFCC to KFCC interface. Three different types of concrete grade (25, 35, and 45 MPa) were produced for the KFCC and one type of concrete grade (35 MPa) for the substrate PC. The outcome of the test showed that KFCC had an excellent interlock with the surface of the PC substrate, and thus, gives bond strength greater than the strength of PC. New concrete with the highest concrete grade of 45 MPa ensued in high compressive, tensile and shear bond strength.